The “Head of the Philosopher” from Porticello: Proposal for the Identification - Castrizio, Daniele (Actual Problems of Theory and History of Art, 2021)
The history of the accidental discovery of the Porticello wreck in Villa San Giovanni is long and complex. The wreckage was found fortuitously in 1969 by a local diver, and the following year it was studied by an underwater excavation mission of the University of Pennsylvania Museum. Thanks to this research, we know that the ship sank in the waters of the Strait between 400 and 375 BC. We also know that it carried various amphorae types, as well as achromatic inkwells and small ingots. Together with these materials, the archaeologists recovered parts of bronze statues, demolished, and systematically broken into pieces. They are not ancient statues ruined by the passage of time: both the “Porticello Philosopher” and the “Head of Basilea” are real masterpieces of Greek classical art, which, given their conservation conditions, have not been exhibited for a long time.It is surprising how, in the scientific debate on the Porticello wreck, the history of the discovery site has never been considered. The name itself, Porticello (in Italian: “small port”) makes us understand its ferry landing function. The study of the sources and the surface archaeological investigations allow us to give an ancient name to the locality: the Roman statio of Ad statuam, Ad columnam.There were many hypotheses made by specialists: Brunilde Sismondo Ridgway has hypothesized a group including Achilles, an unknown character, and the centaur Chiron (the “Porticello Philosopher”), with features considered “monstrous”. Enrico Paribeni proposed a statuary group, with an old man leaning on a stick. Ross Holloway speculated a portrait of Charondas of Catania, author of the political constitution at Rhegion. Angelo Maria Ardovino identifies in the bronze head simply a philosopher. Joseph Frey was thinking of the portrait of the Greek tragedian Sophocles. Paolo Enrico Arias thought to a portrait of the poet Hesiod. Other hypotheses speak generically of a prophet, remembered in one of the ancient epic cycles.Aiming to give a name to the philosopher depicted with such physiognomic precision, our research will begin with a reading of the signs left in the bronze statue, trying to give each one an interpretation. Our goal is to provide the integration of what was present on the statue, but which has been lost. In the end, the comparison with other ancient statues allows us to hypothesize the portrait of the philosopher Pythagoras of Samos.
Keywords: Greek archaeology; iconography; Greek art; Porticello’s wreck; Greek bronze statues